Evaluating the Implementation of the Local Regulations (Qanun) to Control Productive Female Cattle and Buffaloes in Aceh Besar - Samadi Samadi; Sugito Sugito; Yoga Saputra (ANIMAL PRODUCTION, 2022)
The purpose of this study was to evaluate the implementation of Qanuns (local regulations) for controlling productive cattle and buffalo in Aceh Besar District. This study conducted a census of abattoir officers to 10 respondents and 10 muge (intermediaries) to collect data on the population in this study involving all groups of cattle and buffalo farmers in Aceh Besar district, namely 627. The number of samples was determined based on the Slovin formula, i.e., 93 farmers with a 5% error rate. Also, a survey was conducted on six sub-districts in Aceh Regency based on a cluster sampling system. Data processing was done by calculating the percentage of measured parameters and presented in tabular form. The results of the study indicated that the implementation of Qanun decreased the slaughter of productive female cattle and buffalo in Aceh Besar District. However, public understanding of the control of productive female cows/buffalo Qanun remained low because only 30.98% of the public were aware of the Qanun. The lack of knowledge was indicated by the high slaughter and sales of productive female cattle and buffalo at the farmer level that only decreased by around 5.84% (from 70.88% to 65.04% after the implementation of Qanun. Economic needs were the reason for the high sales of productive female cows/buffaloes (73.13%). The weak implementation of Qanun on productive cattle and buffalo was probably due to poor socialization of Qanun for controlling productive cattle and buffaloes. 79.65% of the respondent group answered that they had never received socialization on controlling productive female cattle and buffalo. However, the contributing factors to the declining slaughter and sales of productive female cattle and buffalo since the introduction of Qanun were the strict regulations at the abattoir and the level of knowledge of the abattoir staff regarding Qanun to maintain productive cattle and buffaloes.